Exploring the genetic frontier: Unraveling ANRIL, PAI-1, and HNF1α in stroke progression - Abdullah Hamadi; Rashid Mir; Osama M. Al-Amer; Mohammed Alasseiri; Gasim Dobie; Imadeldin Elfaki; Waseem AlZamzami; Sael Alatawi; Atif Abdulwahab A. Oyouni; Mohammad A. Alanazi; Saravanan Muthupandian (PLoS ONE, 2025)
Background Ischemic stroke poses a notable global public health challenge, with the Kingdom of Saudi Arabia (KSA) being no exception. This multifaceted condition is affected by a combination of factors, including hypertension, diabetes, and genetic influences. The purpose of the present study was to examine the linkage of long noncoding RNAs (such as ANRIL), plasminogen activator inhibitor-1 (PAI-1), and hepatocyte nuclear factor 1 alpha (HNF1α) gene variations with stroke. Leveraging a substantial cohort comprising both stroke patients and healthy individuals from KSA, our research revealed numerous uncommon genetic variations linked to an increased predisposition to stroke. This insight enhances our comprehension of stroke’s genetic underpinnings and can be invaluable in formulating preventive measures, not only in KSA but also on a global scale. Methods In this study we included 100 stroke patients and 100–120 healthy controls from Saudi population. We utilized the amplification refractory mutation system-PCR to genotype the chromosome 9p21 locus, the long noncoding RNA-ANRIL (lncRNA-ANRIL), Hepatocyte Nuclear Factor 1 alpha (HNF1α-A > C [p.I27L]) gene, and the plasminogen activator inhibitor-1 (PAI-1) gene to investigate the association of these gene variations with a stroke. Additionally, WES was performed for 10 stroke patients using the Illumina NovaSeq 6000 platform. Results Our investigation revealed significant associations between stroke patients and healthy controls concerning polymorphic variants of lncRNA-ANRIL (A > C), ANRIL (G > A), HNF1α-A > C, and PAI-1-4G > 5G genes (p < 0.05). Notably, the ANRIL rs1333048-GA genotype exhibited a strong connection with stroke susceptibility in both codominant (OR 2.29, RR 1.54, P < 0.007) and dominant (OR 1.83, RR 1.35, P < 0.034) models, while an overdominant inheritance model demonstrated a protective correlation (OR 0.42, RR 0.64, p < 0.004). Similarly, the ANRIL rs10757278-GG genotype was significantly associated with stroke susceptibility in the codominant (OR 2.80, RR 1.66, P < 0.004) and recessive (OR 3.14, RR 1.62, P < 0.0003) models, with the G allele also displaying a significant association. The HNF1α-TT genotype strongly correlated with stroke risk in the codominant (OR 18.36, RR 9.96, P < 0.048) and recessive (OR 22.14, RR 10.18, P < 0.034) models, with the HNF1α-T allele following a similar trend. The PAI-1-4G-5G genotype was also linked to stroke predisposition (OR 2.09, RR 1.34, P < 0.034) and an increased risk in the dominant model (OR 2.27, RR 1.43, P < 0.006). Furthermore, our study identified several novel and common gene variants in stroke patients through WES, including COL4A2, PSEN2, NOTCH3, and RNF2. Conclusion Our findings underscore the significant role of genetic determinants in chromosome 9p21, the lncRNA-ANRIL, HNF1α-A > C (p.I27L), and PAI-1-4G > 5G genes in elevating the risk of stroke. Additionally, we report low, novel, and intermediate-genetic-risk variants in COL4A2, PSEN2, NOTCH3, and RNF2 through WES, emphasizing the need for further investigation in larger cohort studies.